Economic slowdown in China: Current assessment and global implications - Klaus-Jürgen Gern; Philipp Hauber; Galina Potjagailo (Kiel Institute for the World Economy (IfW), 2015)
After three decades of double digit growth the Chinese economy has become the second largest economy in the world and the most important contributor to global growth. However, in recent years the Chinese economy has slowed substantially. While official numbers for GDP growth report output growth that is still in line with the government's - downwardly adjusted - growth target, alternative indicators of economic activity suggest an even stronger deceleration. In addition, the huge level of debt piled up in recent years in combination with a correction in property prices and - more recently - equity prices have raised fears of a financial meltdown. Against this backdrop, in this note we discuss the current state of the Chinese economy and the risks for the global economy associated with a "hard landing", a sudden pronounced drop in growth rates.
Keywords: 330